ANALISIS EFEKTIVITAS & KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KOTA BANJARMASIN - Rahmiatul, Monica; Prihatiningrum, Raden Roro Yulianti; Rusdayanti Asma (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2022)
In connection with this research, this research was carried out to determine the extent of the effectiveness and contribution of local taxes to local original income (PAD) in Banjarmasin City. Secondary data from BPKPAD was used for the 2018-2022 period, showing good effectiveness in 2018-2021, but experiencing a decline in 2022. More appropriate evaluations and strategies need to be developed to achieve optimal effectiveness in collecting regional tax revenues. More appropriate evaluations and strategies need to be developed to achieve optimal effectiveness in collecting regional tax revenues. Despite fluctuations, the overall regional tax contribution is still classified as "Very Good" to the PAD of Banjarmasin City.